(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
In the evolving landscape of the travel industry, cultural tourism has emerged as a significant force, captivating the global audience with its rich, immersive experiences. Among the myriad elements that embellish this form of tourism, ethno sports play a pivotal role, offering a vibrant spectacle that bridges the past and present while fostering a deeper connection with local cultures. Such activities not only contribute to the diversification and enrichment of the tourist experience but also underscore the importance of cultural tourism in sustaining heritage and fostering mutual understanding among various communities.